Methods of designing digital self-checking automate - Мирошник, М.А.; Кулак, Э.Н.; Алиева, Егана Мовсум; Караман, Д.Г.; Пахомов, Ю.В. (Radiotekhnika, 2016)
The concept of the class of self-checking digital devices designed automate model that provides properties of self-checking is introduced and justified as a result of the research. The method of designing self-checking machines, based on a combination of functional and test procedures of diagnosis, using of methods of synthesis of a fully self-checking circuits and synthesis of circuits embedded control test using a compact test methods. The developed method of designing self-checking machines, is based on a combination of functional and test procedures of diagnosis, using of methods of synthesis of a fully self-checking circuits and synthesis of circuits embedded control test using a compact test method. The method of designing a self-checking automate is developed, based on self-checking and functional test procedures and diagnostic using synthesis methods of completely self-checking circuits and circuits of embedded test methods using control with a compact testing is elaborared in the work. Proposed method is versatile and could be used both for digital control system design and for design of reliable cryptographic data protection modules.